2022
DOI: 10.3390/ijerph191811236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Three-Month HOPSports Brain Breaks® Intervention Program on the Physical Fitness Levels of Grade 6-Learners in South Africa

Abstract: Despite the numerous health benefits of being physically active, children are not active enough. Various researchers have indicated that intervention programs improve physical fitness levels. Still, only a few have focused on improving physical fitness levels by incorporating technology. HOPSports Brain Breaks® are designed and presented as physical activity solutions with online videos requiring the participants to imitate the movements. These videos are 2–5-min classroom activity breaks. This study determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…One of the reasons for the fitness improvements observed in the experimental group could be that, after the children watched the videos, they made a connection between the importance and benefits of PA and actually increased their own PA. Other research has also revealed that the BB videos were effective in increasing students’ self-efficacy levels in learning about PA and health (Uzunöz et al, 2017), in understanding the benefits of a healthy life (Emeljanovas et al, 2014; Tumynaite et al, 2014; Van Biljon & Longhurst, 2010), and in positively changing their attitudes towards health (Bonnema et al, 2020). In a study carried out by West and Shores (2014) to investigate the effects of the BB PA videos on the PA level of seventh- and eighth-grade students, there was an increase in the duration of student participation in moderate to vigorous activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons for the fitness improvements observed in the experimental group could be that, after the children watched the videos, they made a connection between the importance and benefits of PA and actually increased their own PA. Other research has also revealed that the BB videos were effective in increasing students’ self-efficacy levels in learning about PA and health (Uzunöz et al, 2017), in understanding the benefits of a healthy life (Emeljanovas et al, 2014; Tumynaite et al, 2014; Van Biljon & Longhurst, 2010), and in positively changing their attitudes towards health (Bonnema et al, 2020). In a study carried out by West and Shores (2014) to investigate the effects of the BB PA videos on the PA level of seventh- and eighth-grade students, there was an increase in the duration of student participation in moderate to vigorous activities.…”
Section: Discussionmentioning
confidence: 99%
“…PE teachers, who play an essential role in the planning, implementation, and evaluation of PE, must use supplementary resources in their lesson plans to teach PA concepts. Within this literature, studies have emphasized that short video-based Brain Break (BB) videos have positive effects on increasing children’s PA levels (Uzunöz, et al, 2017; Chin et al, 2012; Bonnema et al, 2020). The videos in the Brain Break Physical Activity (BB PA) program (HOPSports, n.d.) are included in a technology supported platform that encourages students to increase their PA levels, and this method of instruction can be applied both in the classroom and at home (Popeska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as a substantial portion of these mental health repercussions stems from heightened socioeconomic instability, public health policies and interventions should prioritize economic revitalization for youth in the region. This involves nancial support for youth and their families, educational and career development programs, and initiatives promoting health and wellness, including access to nutritious food [46], physical activity [47], and comprehensive support [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as a substantial portion of these mental health repercussions stems from heightened socioeconomic instability, public health policies and interventions should prioritize economic revitalization for youth in the region. This involves nancial support for youth and their families, educational and career development programs, and initiatives promoting health and wellness, including access to nutritious food [46], physical activity [47], and comprehensive support [48,49].…”
Section: Discussionmentioning
confidence: 99%